Temperature and water limitation exhibit divergent controls on grassland greening across global aridity gradients - Gongxin Wang; Changqing Jing; Xiuliang Yuan; Tim Van de Voorde; Yuqing Shao; Tong Dong; Ping Dong (International Journal of Applied Earth Observations and Geoinformation)
Grasslands play a crucial role in carbon cycling, biodiversity conservation, and human welfare. Identifying the drivers of grassland greening is essential for forecasting ecosystem responses to future climate change and developing effective adaptation strategies. Grasslands worldwide have experienced pronounced greening trends over recent decades. Despite this widespread phenomenon, the underlying biophysical mechanisms and dominant drivers remain insufficiently understood. By integrating satellite observations with model simulations, we show consistent increases in global grassland leaf area index (LAI) across both historical periods and future scenarios. A sustained increase in summer LAI is identified as the primary driver of grassland greening, contributing approximately 43.28% to the overall trend. Grassland greening exhibits strong spatial heterogeneity, with humid regions accounting for the largest contribution (i.e., 67.27%). Correlation analysis, structural equation modeling, and ridge regression reveal distinct regional differences in the dominant drivers across aridity gradients. Soil moisture (SM) emerges as the primary driver in arid regions, while temperature plays a more prominent role in semi-arid areas. In sub-humid and humid regions, vapor pressure deficit (VPD) exerts a stronger influence on grassland LAI dynamics. Moreover, the synergistic effect of temperature and VPD enhances summer greening, particularly in humid regions and high-latitude areas of the Northern Hemisphere. Notably, the influence of VPD transitions from inhibitory in arid regions to facilitative in humid environments. In contrast, the role of SM in shaping vegetation dynamics weakens progressively along the aridity gradient. These findings advance our understanding of how grassland ecosystems respond to varying hydroclimatic conditions and offer key insights for forecasting vegetation dynamics under future climate change.